Does organizational citizenship behavior predict organizational commitment of employees in higher educational institutions? - Nguyen, Phuong Ngoc-Duy; Tran, Vi Dieu; Le, Dong Nguyen-Thanh (Frontiers in Education, 2022)
Many studies have been conducted in organizations on the topics of organizational commitment and organizational citizenship behavior (OCB). However, there is a shortage of these topics in higher education institutions in the Asian context. Therefore, this article attempts to fill this literature gap. The study examines the influence of organizational citizenship behavior on organizational commitment in the higher education sector in Vietnam. It analyzes the effect of OCB components on three aspects of organizational commitment: affective commitment, normative commitment, and continuance commitment. A self-administered survey was collected from 301 employees working for 21 higher education institutions in Ho Chi Minh City, Vietnam, and the structural equation was analyzed by using Smart PLS-SEM. The results establish that OCB components such as helping, sportsmanship, loyalty, individual initiative, compliance, civic virtue, and self-development influence organizational commitment. Furthermore, “helping” demonstrated the most substantial effect on organizational commitment. The research also found a difference in organizational commitment between groups of respondents based on age and educational level. However, the research was restricted to Ho Chi Minh City universities and future research could broaden the sample size to vocational colleges as well as other Asian contexts. Theoretical contributions, practical implications, and future research directions are discussed.